Cobalt-free niobium-doped barium ferrite as potential materials of dense ceramic membranes for oxygen separation - Xu, D.; Dong, F.; Chen, Y.; Zhao, B.; Liu, Shaomin; Tade, Moses; Shao, Zongping (Elsevier BV, 2014)
Cobalt-free perovskite-type oxides with the nominal composition of BaNbyFe1−yO3−δ (y=0.025–0.20) are synthesized and evaluated as materials used in ceramic membranes for oxygen separation. The effects of Nb-doping on the crystal structure, surface morphology, electrical conductivity, chemical bulk diffusion and surface exchange, and oxygen permeability of the oxides are systematically investigated using XRD, SEM, four-probe DC conductivity, electrical conductivity relaxation technique, and oxygen permeation studies. A small amount of Nb-doping induces a sharp increase in electrical conductivity. A further increase in the Nb-doping amount, however, lowers the electrical conductivity as a result of the blocking effect of Nb5+ on electronic conduction. A small amount of Nb-doping has less impact on the sintering capability. From the oxygen permeation test, it was found that Nb-doping could significantly enhance the oxygen permeability, especially below 750 °C. Among all of the compositions, BaNb0.05Fe0.95O3−δ shows the highest oxygen permeation fluxes, reaching 1.35 and 0.61 mL cm−2 min−1 for a membrane with a thickness of 1.0 mm at 900 and 700 °C, respectively. Furthermore, the membrane is rate-controlled mainly by bulk diffusion, indicating the potential to further improve the oxygen permeation flux via a thinner membrane.